Androgens upregulate Cdc25C protein by inhibiting its proteasomal and lysosomal degradation pathways. - Yu-Wei Chou (PLoS ONE, 2013)
Cdc25C is a cell cycle protein of the dual specificity phosphatase family essential for activating the cdk1/Cyclin B1 complex in cells entering into mitosis. Since altered cell cycle is a hallmark of human cancers, we investigated androgen regulation of Cdc25C protein in human prostate cancer (PCa) cells, including androgen-sensitive (AS) LNCaP C-33 cells and androgen-independent (AI) LNCaP C-81 as well as PC-3 cells. In the regular culture condition containing fetal bovine serum (FBS), Cdc25C protein levels were similar in these PCa cells. In a steroid-reduced condition, Cdc25C protein was greatly decreased in AS C-33 cells but not AI C-81 or PC-3 cells. In androgen-treated C-33 cells, the Cdc25C protein level was greatly elevated, following a dose- and a time-dependent manner, correlating with increased cell proliferation. This androgen effect was blocked by Casodex, an androgen receptor blocker. Nevertheless, epidermal growth factor (EGF), a growth stimulator of PCa cells, could only increase Cdc25C protein level by about 1.5-fold. Altered expression of Cdc25C in C-33 cells and PC-3 cells by cDNA and/or shRNA transfection is associated with the corresponding changes of cell growth and Cyclin B1 protein level. Actinomycin D and cycloheximide could only partially block androgen-induced Cdc25C protein level. Treatments with both proteasomal and lysosomal inhibitors resulted in elevated Cdc25C protein levels. Immunoprecipitation revealed that androgens reduced the ubiquitination of Cdc25C proteins. These results show for the first time that Cdc25C protein plays a role in regulating PCa cell growth, and androgen treatments, but not EGF, greatly increase Cdc25C protein levels in AS PCa cells, which is in part by decreasing its degradation. These results can lead to advanced PCa therapy via up-regulating the degradation pathways of Cdc25C protein.